Mistakes were made (but not by me) - Tavris, Carol; Aronson, Elliot (New York Harper Collins Publishers, 2020)
Renowned social psychologists Carol Tavris and Elliot Aronson take a compelling look into how the brain is wired for self-justification. This updated edition concludes with an extended discussion of how we can live with dissonance, learn from it, and perhaps, eventually, forgive ourselves.
Keywords: BUSINESS & ECONOMICS: Decision-Making & Problem Solving; SELF-HELP: Creativity; Social Psychology